Cutaneous manifestations among Egyptian children and adolescents with type 1 diabetes - Randa M. Youssef; Amany Ibrahim; Iman M. Amin; Hend M. Soliman; Amany Ali (SpringerOpen, 2016)
Background: Although almost all patients with T1DM eventually develop one or more skin manifestations, data on cutaneous manifestations of type 1 diabetes mellitus (T1DM) are scarce. They can be the first presenting sign, or even precede the diagnosis or develop from the long-term effects of diabetes. Objective: To detect the prevalence and spectrum of skin manifestations in children and adolescents with T1DM attending the DEMPU clinic, Cairo University and to investigate the effect of the disease duration on these dermatoses. Subjects and methods:Two hundred twenty-five children and adolescents with T1DM were examined for dermatological problems. Of them, 152 patients who had cutaneous manifestations with T1DM were included in this case-control study, 152 age and sex matched non diabetic patients were included as control group. A detailed dermatological examination was carried out by the dermatology team. Results: The overall prevalence of dermatologic manifestations was 67.56% (152 T1DM patients; 74 males and 78 females). The mean age of the patients was 8.38 ± 3.79 years and the mean diabetes duration was 2.80 ± 2.86 years. Cutaneous adverse effects related to insulin injections were the most common manifestation representing 28.9%, followed by cutaneous infections (bacterial, fungal and viral infections) in 25%, allergic skin diseases in 19.1% and pruritus in 15.1% of patients with T1DM. Conclusion: Broad spectrums of dermatoses are common (67.56%) in Egyptian patients with T1DM. Early referral to the dermatologist helps to detect skin complications of diabetes in these children and is essential for both prevention and management of these conditions.